193k views
4 votes
83x - 6) = 6(4x + 8)​

1 Answer

6 votes

Answer:


x = (54)/(59)

Explanation:

I'm assuming you meant (83x - 6). Either way, the parentheses aren't needed there as there aren't any numbers outside of the parentheses on that side of the equation.

So:

Remember PEMDAS

P – Parentheses

E – Exponents

M – Multiplication /D – Division (whichever comes first from left to right)

A – Addition /S – Subtraction (whichever comes first from left to right)

Nothing needs to be distributed on the left side, so let's distribute the right side.

6(4x + 8)

6 * 4x = 24x

6 * 8 = 48

Now we have 24x + 48

83x - 6 = 24x + 48

Now, we must isolate the x so that in the end, we can get x =

83x - 6 = 24x + 48

+ 6 +6

83x = 24x + 54

-24x -24x

59x = 54

Now, we have isolated the x! Finally, we want x to = 1 so that it will be x = instead of 59x =.


(59x)/(59) = (54)/(59)

Because 54/59 does not divide into a rational number or simplify any further, we can keep it as a fraction.


x = (54)/(59)

~
InLoveWithPugs

Moderator

Math Enthusiast

User CDspace
by
4.7k points